Solution of Turbine Blade Cascade Flow Using an Improved Panel Method - Zong-qi Lei; Guo-zhu Liang (International Journal of Aerospace Engineering)
An improved panel method has been developed to calculate compressible inviscid flow through a turbine blade row. The method is a combination of the panel method for infinite cascade, a deviation angle model, and a compressibility correction. The resulting solution provides a fast flexible mesh-free calculation for cascade flow. A VKI turbine blade cascade is used to evaluate the method, and the comparison with experiment data is presented.